Pemberdayaan Masyarakat melalui Sosialisasi Pemanfaatan Pupuk Organik Padat Kohe Kambing dan Agens Hayati Mikoriza sebagai Alternatif Pertanian Berkelanjutan - Khotim Fadhli; Ma’rifatul Khomsah; Ramadhan Galang Pribadi; Kholis Firmasyah (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2021)
This KKN - PPM aims to increase the knowledge of farmer groups in Barongsawahan Village through socialization on the use, manufacture and application of solid organic fertilizers from goat manure and Mycorrhizal Biological Agents in Barongsawahan Village. In Brongsawahan Village, there are 3 hamlets, namely, Dusun Sawahan, Dusun Barong, and Dusun Jayan. The activity method is carried out by the socialization method. The response from the KKN-PPM partners was very positive. Farmers are also very enthusiastic about making organic fertilizers as an alternative to using chemical fertilizers that have been going on for a long time in Barongsawahan Village and as a new business opportunity. The output of this activity is knowledge of the manufacture, benefits and application of solid organic fertilizers from goat manure and Mycorrhizal Biological Agents so as to reduce dependence on chemical fertilizers. This activity was carried out with the hope that the Barongsawahan Village farmers would be able to switch to the use of organic fertilizers and biological agents. Keywords: Socialization, Solid Organic Fertilizer From Goat Manure, Mycorrhizal Biological Agents